MASTER TRAINING: TRADITION AND INNOVATIONS - Audrey A. Baykov; Oleg B. Pichkov (Moscow Polytechnic University, 2016)
Moscow State Institute of International Relations (University) is a leading Russian educational and scientific center, following the latest educational trends. For all its history, MGIMO-University is continuing to remake itself and today it offers more than forty MA programs taught both in Russian and English. The article presents unique advantages and opportunities provided by MGIMO to its students. Moreover, it focuses on the widest range of MA programs available in a university of its type anywhere.